TRADE BALANCE AND UNEMPLOYMENT IN JORDAN - Alawin, Mohammad (European Scientific Journal, ESJ, 2013)
This paper presents theoretical and empirical evidence on the nature of the relationship between trade balance and unemployment rate in Jordan for the period 2000:Q1-2012:Q2. The major finding of this paper indicates an absence of a long-term relationship between the variables of interest. However, the results show that deficit in trade balance causes unemployment, and unemployment causes a deficit in trade balance in the short-run. This indicates that, in the short-run, trade liberalization is able to increase aggregate productivity in some sectors and able to increase efficiency of economic performance in terms of employment opportunities in Jordan.